Peculiarities of Web Site Quality Evaluation - Ruževičius, Juozas; Guseva, Natalija (Ekonomika, 2006)
This article finds methods and techniques of web site quality evaluation. One of the most important activity areas for each organization is information distribution and communication with clients. For this purpose the Internet products, such as web sites, portals, e-catalogues and e-shops are created. It is a relatively cheap and interactive tool for advertising, informing, communication with clients and sales. In Lithuania web site is the most often used form of Internet product. That is why it is important to give a definition for web site quality, to outline its most important dimensions, to find out consumers’ expectations and priorities. It’s equally important for the consumers and the developers.In Lithuania, there is no common web site quality evaluation criteria, techniques or system of tools. Thus, there is created and sold product, web site, but there are no clearly described its quality requirements. Therefore this product’s expansion and commercialisation difficulty. The problem of web site quality evaluation should be analysed from different scientific, methodological and technical points. Web site is a complicated system consisting of interrelated elements. That is why to evaluate its quality, a set of criteria and tools is necessary. The purpose of the present work was to disclose the contents of web site quality, to prepare its evaluation technique and to carry out a case study based on this technique. The publication is based on analysis of scientific and methodical literature. on the authors’ quality research results. The evaluation of web site quality was based on the experts’ and users’ interrogatory and on testing by Validator, Temesis, Watchfire mechanisms.A web site quality evaluation technique was created; it was used in Vilnius University web site quality research. The aim was to find out web site quality evaluation from actors’ position. This will aUow to analyze the gap between the users’ and the creators’ perception of web site quality, to identify users’ and creators’ priorities in site quality evaluation, and to find ways of harmonization between users’ specific needs and creators’ goals. Suggestions for the web site visibility, perception, technique, content and services improving were prepared. The proposed technique is intended not only for web site quality evaluation, but also for revealing its shortcomings. identifying the users expectations and priorities. The authors believe that the results of the study give useful guidelines on how to improve the quality of companies’ web sites.